Effect of Sb incorporation on thermo-mechanical properties of amorphous Se-Te-Sn alloys. (20th June 2018) - Rao, Vandita; Mehta, N; Kumar, Amit; Dwivedi, D K
Abstract: In present paper, bulk Se78−x Te20 Sn2 Sbx (x = 0, 2, 4 & 6) amorphous alloys were developed by melt quench technique. The synthesized samples were characterized by means of XRD and DSC techniques for structural and phase transformation analysis respectively. Hardness behavior was investigated by calculating Vickers hardness number and other thermo-mechanical parameters to examine the effect of Sb in Se-Te-Sn parent alloy.